Designing Thai literature learning in a multicultural of Thai language teachers at the secondary education level - Kongklay, Katekaw; Kongpan, Natchaphon (Journal of Multidisciplinary Academic Research and Development (JMARD), 2024)
The research objectives were to survey the design of Thai literature learning in a multicultural of Thai language teachers at the secondary education level. The method of this research was in-depth interviews with 30 Thai language teachers chosen by cluster random sampling from Thai language teachers in 6 regions: Northern, Central, Northeastern, Eastern, Western, and Southern, amounting to 5 teachers per region. In this research study, the tool that were used to collect data were the in-depth interview, which is an open-ended question, has a reliability of .83. The results of the research found that methods for designing learning activities for Thai language teachers are different according to the context of each area, as follows: 1) The Northern region uses field trips and technology media, 2) The Central region uses field trips and integrated learning, 3) The Northeastern region uses the field trip method, 4) The Eastern region organizes problem-based learning and uses technological media, 5) The Western region organizes problem-based learning and cooperative learning, and 6) The Southern region organizes learning cooperative and field trip methods. The methods for designing learning activities can be classified into 5 groups: 1) problem-based learning management, 2) field trips, 3) collaborative learning management, 4) learning management using technological media, and 5) blended learning management. The results of this research will serve as guidelines for multicultural Thai literature learning for teaching multicultural Thai literature to Thai language teachers at the secondary school level in order to meet the cultural diversity of students and society.